Dr. Daniel Ceradini — Deep Plane Facelift — New York - Ceradini, Daniel (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Daniel Ceradini, practicing in New York, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002947; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; new york